Gambaran Motivasi Kerja dan Work Engagement Ditinjau dari Urutan Kelahiran Karyawan - Mutiara Mirah Yunita (Jurnal Ilmiah Psikologi MIND SET, 2019)
Companies often have experiences problem due to low motivation in employee. There are various factors that can influence. One of them is the individual's personality which is also formed from the birth’s order. The results of this research showed that the variable work motivation, single child and first child had the highest value. Then in the work engagement variable, the only child and the first child have the highest value. Whereas in the dimension of vigor, single children and middle children have the highest value. Then in the dimension of dedication, the first child and the last child have the highest value. In absorption, the first child and the last child have the highest value. The implication in this study is that companies can consider the birth order as a means of placing employees in a position. In addition, the results of this study are expected to lead a supervisor to predict employee motivation and work engagement in work. In addition, companies can develop learning strategies in the face of low motivation and work engagement in accordance with the birth order.